PENGARUH KARAKTER PERSONAL, REPUTASI, DAN SELF ESTEEM TERHADAP SENJANGAN ANGGARAN - Wiswa Netra, Ida Bagus; Damayanthi, I Gst Ayu Eka (E-Jurnal Akuntansi; Vol 19 No 2 (2017), 2017)
The budget process are affecting the behavior of individuals to undertake budgetary slack. The purpose of this study was to determine the influence of personal character, reputation and self-esteem of the budgetary slack in Klungkung regency. The population in this study is the Head of Department, Head of Sub Division of Finance, and Head of Sub Division of Planning contained in Department 12 in Klungkung regency. The method used in the determination of the sample is nonprobability sampling method with purposive sampling technique. The data collection was conducted by questionnaire. The analysis technique used is multiple linear regression. Based on the analysis found that variables personal character, reputation and self-esteem negatively affect budgetary slack, which means that the more optimistic personal character possessed the possibility of budgetary slack would be lower. The higher the reputation and self-esteem, then the possibility of budgetary slack became .
Keywords: Budgetary slack, personal character, reputation and self-esteemy